Anaphylactic Shock Due to Atracurium in a Patient Underwent General Anesthesia - Ryalino, Christopher; Labobar, Otniel Adrians; Wiryana, Made; Sinardja, I Ketut; Senapathi, Tjokorda Gde Agung; Pradhana, Adinda Putra (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Anaphylaxis is a systemic hypersensitivity reaction marked by life-threatening, rapid onset of the airway, breathing, and circulation problems. Despite its rare incidence, without proper treatment, it may cause fatality. CASE REPORT: In this report, we present a 19-year-old female with an infected ovarian cyst, who was scheduled for gynecologic laparotomy. In pre-operative assessment, she was classified as an American Society of Anesthesiologist (ASA) one patient without any history of drug or food allergy. Hemodynamic changes occurred on anesthesia induction after the administration ofatracurium, a muscle relaxant agent. Marked clinical signs were wheezed-bronchospasm, dyspnea, hypersalivation, desaturation, tachycardia, hypotension, and systemic erythema. She was diagnosed with anaphylactic shock. We provided 100% oxygenation, fluid resuscitation, epinephrine, and supportive therapy by anaphylaxis guidelines. Respiratory and cardiovascular functions stabilized 2 h post-resuscitation. The surgery was canceled, and she was observed in ICU for 24 h. CONCLUSION: Timely diagnosis and early resuscitation are key factors determining the outcome of an anaphylactic reaction.